Research Of the Influence of OpokaLike Rocks on The Physical and Mechanical Properties of Portland Cement - Mukhiddinov Dilshod Davronovich; Iskandarova Mastura Iskandarovna (Genius Journals, 2021)
This article is devoted to the study of technological properties of opoka-like rocks of Uzbekistan and their influence on physical and mechanical indices of Portland cement of JSC "Kizilkumcement.
Keywords: Additive for cement; pozzolanic additives; opoka-like rock, clinker; physical-chemical properties